2021
DOI: 10.1111/jzo.12866
|View full text |Cite
|
Sign up to set email alerts
|

Traffic noise drives an immediate increase in call pitch in an urban frog

Abstract: Noise pollution is an underappreciated component of global environmental change and can impact species that have a strong reliance on acoustic communication. In urban areas, traffic noise can interfere with the ability of animals to communicate and complete essential aspects of their daily lives. We investigated the impact of traffic noise on the calling behaviour of the brown tree frog (Litoria ewingii) in south‐eastern Melbourne, the fastest‐growing human population centre in Australia. We placed six acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…And changes in signals due to changes in habitat, for instance, through urbanization, are becoming more widely researched and provide more examples of how selection pressures can result in sexual signaling that compensates for the surrounding environment. Anurans, in particular, have demonstrated a change in call rate or call complexity in response to novel selection pressures introduced by an urban environment [157][158][159][160][161].…”
Section: Predicting Through Patternsmentioning
confidence: 99%
“…And changes in signals due to changes in habitat, for instance, through urbanization, are becoming more widely researched and provide more examples of how selection pressures can result in sexual signaling that compensates for the surrounding environment. Anurans, in particular, have demonstrated a change in call rate or call complexity in response to novel selection pressures introduced by an urban environment [157][158][159][160][161].…”
Section: Predicting Through Patternsmentioning
confidence: 99%
“…Many insects, anurans, birds, and mammals use acoustic signals to attract mates and protect their territory [8,9]. However, anthropogenic noise, anthropogenic substrate-borne vibrations, light pollution, and habitat change resulting from urbanization affect the production, transmission, and reception of acoustic signals [10][11][12][13]. For example, studies reported that birds vocalized at higher dominant frequencies and sound levels in urban areas than in forests because of background noise [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies found that anthropogenic noise had a significant effect on frog-calling parameters and behaviors in the urban environment. For example, Higham et al [10] found that traffic noise increased the call pitch of brown tree frogs (Litoria ewingii) in urban areas. Similarly, anthropogenic noise in urban areas also altered the call rate or call duration of frog species [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%